CHANGES IN BIOCHEMICAL CHARACTERISTICS OF THIRTY-SIX IRANIAN WHEAT LANDRACES IN RESPONSE TO DROUGHT STRESS AND THEIR CLASSIFICATION USING MULTIVARIATE ANALYSIS - S. Dorostkar; A. Dadkhodaie; B. Heidari (Journal of Animal and Plant Sciences, 2016)
Drought stress is one of the most important factors limiting crop production in dry regions. In order to study the effects of drought stress on antioxidant enzymes and physiological characteristics, thirty six bread wheat genotypes were evaluated at the research station, School of Agriculture, Shiraz University, Iran during 2010-2011 and 2011-2012 growing seasons. The experiment was conducted as a split-plot design with irrigation treatments (well-irrigation and non-irrigation) as main plots in three replications and genotypes as sub-plots. Water stress was applied when 50% of ears emerged. Two weeks after applying stress, the youngest leaves were collected to extract enzymes. Results showed that the activity of all enzymes increased under stress, with APX and proline showing the highest increase. Therefore, these factors were considered suitable to screen drought tolerant genotypes. The genotypes KC4856, KC4848, KC4512, KC3893, KC3892 and KC4929 had high anti-oxidant activity and high yields but showed a low decrease in MSI and hence were classified as tolerant. These results suggest that oxidative stress tolerance is closely associated with increase in antioxidant enzymes and proline and decrease of MSI.
Keywords: anti-oxidant enzyme; crop production; hexaploid wheat; membrane stability index; proline